2005
DOI: 10.1128/aac.49.7.2895-2902.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identical Penicillin-Binding Domains in Penicillin-Binding Proteins of Streptococcus pneumoniae Clinical Isolates with Different Levels of β-Lactam Resistance

Abstract: We have sequenced the penicillin-binding domains of the complete repertoire of penicillin-binding proteins and MurM from 22 clinical isolates of Streptococcus pneumoniae that span a wide range of ␤-lactam resistance levels. Evidence of mosaicism was found in the genes encoding PBP 1a, PBP 2b, PBP 2x, MurM, and, possibly, PBP 2a. Five isolates were found to have identical PBP and MurM sequences, even though the MICs for penicillin G ranged from 0.25 to 2.0 mg/liter. When the sequences encoding PBP 1a, PBP 2b, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 32 publications
2
39
1
1
Order By: Relevance
“…Isolates of Streptococcus pneumoniae carrying identical PBP sequences can show different levels of ␤-lactam resistance (6). Moreover, the transfer of the pbp genes from a clinical isolate to the laboratory strain R6 resulted in a transformant with a higher level of resistance than that of the donor strain (6). Possibly, genetic factors can either increase or decrease the level of PBP-based resistance in relation to the compatibility of the mutated PBP with other enzymes involved in peptidoglycan synthesis (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolates of Streptococcus pneumoniae carrying identical PBP sequences can show different levels of ␤-lactam resistance (6). Moreover, the transfer of the pbp genes from a clinical isolate to the laboratory strain R6 resulted in a transformant with a higher level of resistance than that of the donor strain (6). Possibly, genetic factors can either increase or decrease the level of PBP-based resistance in relation to the compatibility of the mutated PBP with other enzymes involved in peptidoglycan synthesis (6).…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that the genetic background of strain Rd may modulate the level of resistance to imipenem conferred by PBP 3 on the transformant. Isolates of Streptococcus pneumoniae carrying identical PBP sequences can show different levels of ␤-lactam resistance (6). Moreover, the transfer of the pbp genes from a clinical isolate to the laboratory strain R6 resulted in a transformant with a higher level of resistance than that of the donor strain (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two of the seven steps led to substitutions in Ldt fm , indicating that modifications of other unknown factors are involved in acquisition of resistance. For the DD-transpeptidases, emergence of ␤-lactam resistance also involves a combination of multiple modifications affecting non-penicillin-binding protein factors, several residues of a given penicillin-binding protein, and sometimes several penicillin-binding proteins (11)(12)(13)(14)(15)(16). The requirement for multiple mutations accounts for the relative robustness of ␤-lactams with respect to the emergence of resistance by target modification.…”
Section: Discussionmentioning
confidence: 99%
“…The scenario that different PBP allele combinations confer differing ␤-lactam resistance phenotypes is complicated by the finding that transformations using PBP genes from certain strains were not sufficient to transform wild-type strains to the same high level of resistance (120,121). One study reported that strains exhibiting identical PBP transpeptidase domain sequences exhibited penicillin MICs ranging from 0.25 to 2.0 g/ml (122).…”
Section: Involvement Of Other Proteins In ␤-Lactam Resistancementioning
confidence: 99%